2017
DOI: 10.1371/journal.pone.0175891
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the buffering effect of social support figures: Social support attenuates fear acquisition

Abstract: Social support is associated with positive health outcomes, and research has demonstrated that the presence, or even just a reminder, of a social-support figure can reduce psychological and physiological responses to threats. However, the mechanisms underlying this effect are unclear, and no previous work has examined the impact of social support on basic fear learning processes, which have implications for threat responding. This study examined whether social support inhibits the formation of fear association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 33 publications
1
76
2
1
Order By: Relevance
“…The results supported our hypothesis that the attachment prime inhibited the differential fear response during fear acquisition, and this had long-term effects on the recall of extinction 48 h later. These findings replicate an earlier report that social support figures inhibit fear acquisition when attachment figures are associated with the CS (Hornstein and Eisenberger, 2017 ). This current report extends this previous report by showing that awareness of an attachment figure prior to acquisition, even when the attachment figure is not directly conditioned with the aversive stimulus, limits the extent to which fear is acquired.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results supported our hypothesis that the attachment prime inhibited the differential fear response during fear acquisition, and this had long-term effects on the recall of extinction 48 h later. These findings replicate an earlier report that social support figures inhibit fear acquisition when attachment figures are associated with the CS (Hornstein and Eisenberger, 2017 ). This current report extends this previous report by showing that awareness of an attachment figure prior to acquisition, even when the attachment figure is not directly conditioned with the aversive stimulus, limits the extent to which fear is acquired.…”
Section: Discussionsupporting
confidence: 90%
“…To test the proposal that attachments serve as a unique inhibitor of fear, we aimed to compare the fear inhibitory effects of attachment and positive cues. While Hornstein and Eisenberger ( 2017 ) found that social support cues resulted in greater inhibition of fear relative to strangers, they did not directly compare the inhibitory effects with positive stimuli. Whereas previous studies of attachments as potential safety signals have paired social cues with the CS, we tested the capacity of a brief awareness of attachment figures prior to fear conditioning to limit fear acquisition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One way they can assist patients is to provide social support, which is defined as the “ transactional communicative process, including verbal and non‐verbal communication, which aims to improve an individual's feelings of coping, competence, belonging, and/or esteem” (Mattson & Hall, , p.184). Social support has shown several benefits related to disease outcomes, including lower stress, better medication intake, and disease screening (Hornstein & Eisenberger, ; Martin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Factors influencing fear and behavior in the face of threats may be perceived vulnerability (Weinstein, 2000), social support (Hornstein & Eisenberger, 2017), and close relationships, since they are crucial for well-being and health (Holt-Lunstad, Smith & Layton, 2010). Similarly, attachment style influences affect regulation (Marganska, Gallagher & Miranda, 2013), and insecure attachment has been linked to heightened sensitivity for anxiety (Watt, Lachlan & Campbell, 2005), as well as personal fear of death (Mikulincer, Florian & Tolmacz, 1990).…”
Section: Fear and The Crisismentioning
confidence: 99%